Pseudomonas Volume 7: New Aspects of Pseudomonas Biology - Ramos, Juan-Luis.; Goldberg, Johanna B.; Filloux, Alain; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
Pseudomonas volume 7 collects some of the most relevant and emerging issues in the biology of these microorganisms, and a number of other important issues that were not collected in the previous volumes.   The first six volumes of the Pseudomonas series covered the biology of pseudomonads in a wide range of contexts, including the niches they inhabit, the taxonomic relations among its members of this group, the molecular biology of gene expression in different niches and under different environmental conditions, the analysis of virulence in plants, animal and human pathogens, as well as the determinants that make some of these strains of interesting for biotechnological applications.   This seventh volume covers the following topics: The history of the biology of Pseudomonas The use of Pseudomonas as biological agents New trends in the molecular biology of these microorganisms Pseudomonas and the immune system of insects and animals   This book will be of use to researchers working on these bacteria, particularly those studying medical aspects of Pseudomonas, and their use as a means to control pathogens or to stimulate plant growth. This volume is also interesting for those studying the physiology, genetics, molecular biology of Pseudomonas and those using novel-omics approaches to understand bacteria of the genus Pseudomonas.
Pseudomonas aeruginosa Host Immune Evasion -- Pseudomonas entomophila: a versatile bacterium with entomopathogenic properties -- Pseudomonas Activation of the Inflammasome -- P. aeruginosa type VI secretion machinery: another deadly syringe -- Anaerobic life style of Pseudomonas aeruginosa -- Pseudomonas strains that exert biocontrol of plant pathogens -- Resistance and response to anti-pseudomonas agents and biocides -- Lessons from the QSCR structure for Quorum sensing -- Understanding and Exploiting Bacterial Outer Membrane Vesicles -- Events in root colonization by Pseudomonas putida -- My memories of Pseudomonas in the twentieth century.
Keywords: Medicine; Microbiology; Biomedicine, general; Microbiology